PENGARUH GAYA KEPEMIMPINAN KEPALA DESA TERHADAP PENINGKATAN KUALITAS PELAYANAN PUBLIK DI KANTOR DESA PIMPING KECAMATAN TANJUNG PALAS UTARA KABUPATEN BULUNGAN - Jimmy Nasroen,; Irsyad Sudirman, (Journal of Innovation Research and Knowledge, 2025)
The purpose of this research to know more deeply whether the Leadership’s Style of the Village chief is influential significantlly to Quality improvement of Public Service at Pimping’s Village Office in Subdivision of North Tanjung Palas of Bulungan Regency. The sample which was used in the research were 27 (twenty seven) people, who were gotten by saturated sampling technique or census and purposive sampling technique. The research method is quantitative with approach survey. Next the research data collecting technique used questionnare technique, observation, documentation study. While the research data analysis used a simple regression analysis tool, but in the data management used software program helping of SPSS 20. According the validity test result and independent variable data reliability (X) with dependent variable (Y) it was known that the questionnare data wich was used be proven was valid and reliable until there is no case data that be out (exclude). The similarity shape regression line from 2 (two) the research variable which was used Y=18.436+0.447 X with the sample correlation value (R) between independdents variable with public service quality in the amount of 0,480 which is at the level of correlation is being or neutral. According the analysis result of varians (ANOVA) it was known that the value F count in the amount of 7.478. with the value F table in the amount of 4.242 could be summarized that the value F is bigger than F table with value comparison namely 7.478>4.242. That means The Leadership’s Style is influential significantly the quality raising of Public Service at Pimping’s Village Office in Subdivission of North Tanjung Palas of Bulungan Regency. Next the test result explains that the value of T value in the amount of 2.735 after it was consulted with t table is namely 2.060 for the result both of sides are proven to have the value bigger than the value comparison namely 2.735>2.060 that means that the Leadership Style is influential significantly to the Public Service Quality at Pimping’s Village Office in Subdivision of North Tanjung Palas of Bulungan Regency